Blood biochemical parameters of Murrah buffalo (Bubalus bubalis) reared in the high salinity area of Bangladesh (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: The study’s goal was to determine the impacts of drinking saline water on the biochemical parameters of Murrah buffalo. Materials and methods: Twenty Murrah buffalo of both sexes, ranging in age from 6 months to 11 years, were randomly selected. 10 ml of blood samples were collected from each buffalo and processed to separate serums. The supplied drinking water and feed samples were also collected. Blood parameters–glucose, alanine-aminotransferase (ALT), aspartate-aminotransferase (AST), creatinine, urea, uric acid, magnesium, phosphorous, calcium, zinc, potassium, sodium, and chloride–were analyzed. Different clinical manifestations of selected buffalo were also recorded. Results: The buffaloes with skin lesions had higher serum concentrations of AST, creatinine, zinc, sodium, and chloride compared to another group. Significant age effects were found for serum concentrations of glucose (p < 0.05), creatinine (p < 0.01), uric acid (p < 0.001), phosphorus (p < 0.05), and potassium (p < 0.05). No significant age and gender effects were found for AST, ALT, urea, magnesium, calcium, zinc, sodium, and chloride. The serum concentration of creatinine was higher in female buffaloes, whereas the uric acid concentration was lower in female buffaloes compared to males. Conclusion: The blood parameters that were measured and remained within reference ranges show that Murrah buffaloes can adapt to saline water with little to no impairment to their liver and renal functions. The differences in the ages and sexes of the animals within the study groups highlight that mature female buffaloes suffer more from skin disorders and attempt to adjust to exotic conditions by changing the functioning of their liver and kidney.  J. Adv. Vet. Anim. Res., 9(4): 736–742, December 2022http://doi.org/10.5455/javar.2022.i643